1999
DOI: 10.1097/00000421-199910000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Primary Appendiceal Adenocarcinoma

Abstract: Adenocarcinoma of the appendix is rarely encountered and is usually discovered at the pathology examination of the surgical specimen. Adenocarcinoma of the vermiform appendix is a rare neoplasm and constitutes <0.5% of all gastrointestinal neoplasms. There is no symptom of appendiceal cancer, and it is very difficult to diagnose preoperatively. Most female patients are diagnosed as having a gynecologic disease. Second primary synchronous and metachronous neoplasms, especially in the gastrointestinal tract, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…Appendiceal adenocarcinoma is a rare cancer and constitutes <0.5% of all gastrointestinal neoplasms (32). Because there are no specific or early symptoms, it is very difficult to diagnosis preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Appendiceal adenocarcinoma is a rare cancer and constitutes <0.5% of all gastrointestinal neoplasms (32). Because there are no specific or early symptoms, it is very difficult to diagnosis preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The histopathology and clinical outcomes of appendicular adenocarcinoma have been studied previously, and perforation is known to be common in appendicular adenocarcinoma patients. However, peritoneal implantation due to perforation is discussable (10). Surgical treatment for appendicular adenocarcinoma has controversies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies into the genetic alterations in appendiceal carcinoma has shown that it is distinct from colorectal cancer. [9] The molecular basis for the development of appendiceal mucinous tumours remains unclear. It has been shown that KRAS is frequently mutated in the majority of low-grade appendiceal neoplasms and mucinous adenocarcinomas, whereas GNAS mutation is only observed in of low-grade appendiceal neoplasms.…”
Section: Discussionmentioning
confidence: 99%